Titanium alloy artificial joint and processing method thereof
By designing a specific 3D structure on the titanium alloy artificial joint ball head and filling nanoparticles, the friction and wear problems caused by coating peeling are solved, long-term effective lubrication and antibacteriality are achieved, and the service life of artificial joints is extended.
Patent Information
- Application Number
- CN202510260045.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-15
AI Technical Summary
During use, existing titanium alloy artificial joints are prone to accelerate friction and wear due to peeling of the coating, which in turn causes inflammation and movement disorders.
The titanium alloy ball head was prepared by one-step metal 3D printing method, and the main hole, main channel, support mesh channel and pit structure were designed, and nano-hydroxyapatite, nano-MoS2 and nano-Cu particles were pre-filled in these structures to achieve long-term effective lubrication and antibacterial.
Through this structural design and particle filling, the tribological properties of titanium alloy artificial joints are significantly improved, extending their service life, reducing the risk of wear and inflammation, while enhancing antibacterial properties.
Smart Images

Figure CN119818244A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of artificial joints, and in particular to a titanium alloy artificial joint and a processing method thereof. Background Art
[0002] Artificial joint replacement is an ideal choice for patients with joint damage due to aging or accidents. However, with the widespread use of artificial joints, the compatibility of artificial joints with the human body, joint wear and inflammation caused by them have become issues that need long-term attention and solutions.
[0003] At present, the materials of artificial joints mainly include three categories: metal or alloy materials, organic polymer materials and ceramic materials. Among them, the significant advantages of metal or alloy artificial joints are high forming precision and high strength, among which 316L stainless steel, cobalt-based alloys and titanium alloys are the representatives. However, 316L stainless steel has poor corrosion resistance, and cobalt-based alloys have poor biocompatibility, while titanium alloys have strong biocompatibility and good corrosion resistance, and have better application prospects. For artificial joints, they usually present a variety of different forms based on the different joint positions. Among them, the femoral head artificial joint for the hip joint is mainly composed of a ball head and a head handle. The head handle is used to fix the artificial joint, and the ball head is used to achieve the movement of the joint. For the head handle, the focus is on achieving rapid combination with the bone after implantation and reducing inflammation; for the ball head, how to reduce friction and wear with the acetabulum, reduce wear debris and inflammation caused by it, and thus extend the service life of the ball head is the key.
[0004] For this reason, in the prior art, there are methods such as coating preparation on the surface of titanium alloy artificial joints to modify the surface, such as using surface ion implantation or ion nitriding to improve its wear resistance, using hydroxyapatite coating to improve its osteogenic performance, and using MoS2 coating to improve its antibacterial performance. However, currently, the main method is to cover the surface of the artificial joint with hydroxyapatite coating or MoS2 coating as a whole, that is, the base material of the artificial joint is completely covered. In the actual friction and wear process of the relative movement of the artificial joint, the coating may peel off due to poor bonding strength or local stress concentration, thereby accelerating the failure of the surrounding coating. In addition, when the coating fails, it will also cause a jam to the movement of the ball head, thereby possibly causing movement disorders and inflammation of the artificial joint.
[0005] Therefore, a new titanium alloy artificial joint and a processing method thereof need to be developed to obtain a titanium alloy artificial joint with better performance. Summary of the invention
[0006] The purpose of the present invention is to provide a titanium alloy artificial joint and a processing method thereof, which can effectively promote the osteogenic performance and antibacterial effect of the artificial joint, effectively achieve long-term effective lubrication of the ball head surface, and thereby enable the titanium alloy artificial joint to obtain a longer service life.
[0007] A titanium alloy artificial joint of the present invention adopts the following technical scheme: it includes a titanium alloy head handle and a titanium alloy ball head, and the titanium alloy head handle and the titanium alloy ball head are fixedly connected as one body; at least one main hole is provided in the middle of the surface of the titanium alloy ball head, and a plurality of branch network channels are also provided inside the titanium alloy ball head, and a main channel with a closed bottom is provided inside the titanium alloy head handle; the main hole passes through the titanium alloy ball head and is connected with the main channel inside the titanium alloy head handle; the outer surface of the titanium alloy ball head is also provided with a first pit and a second pit; the diameter of the first pit is 10-100 microns, and the diameter of the second pit is 300-1000 microns; the two ends of the branch network channel are respectively connected with the bottom of the first pit and the main channel; the bottom of the second pit is closed; the outer surface of the titanium alloy ball head is also provided with at least one annular groove with a width not exceeding 100 microns; the main hole, the main channel and the branch network channel are all prepared by a one-step metal 3D printing method; the main channel and the first pit are pre-filled with nano-hydroxyapatite and / or nano-MoS2 particles; the second pit is not filled.
[0008] Furthermore, the main channel, the branch network channel and the first pit are pre-filled with nano Cu particles.
[0009] Furthermore, the main channel, the branch network channel and the first pit are also pre-filled with simulated body fluid.
[0010] Furthermore, the first pit is prepared by laser post-processing; the first pit and the second pit are arranged regularly to form a texture on the surface of the titanium alloy ball head; the second pit is prepared by laser post-processing or by a one-step 3D metal printing method.
[0011] Furthermore, the surface of the titanium alloy head handle is provided with micropores with a diameter of 300-600 microns, and some of the micropores are filled with nano-hydroxyapatite and / or nano-MoS2 particles.
[0012] Furthermore, the diameter of the main hole is 1000-3000 microns; the inner diameter of the main channel is 1000-3000 microns, and the top diameter of the branch network channel is 500-1000 microns.
[0013] Furthermore, the area surrounded by any annular groove has a first pit and a second pit.
[0014] Furthermore, the depth of the first pit is 100-300 microns.
[0015] A method for processing a titanium alloy artificial joint of the present invention comprises the following steps: S1, 3D printing one-step molding to obtain the main body of the titanium alloy artificial joint: using a metal 3D printer and a selective laser cladding process, the titanium alloy head handle and the titanium alloy ball head are printed in one step, a main hole and a second pit are obtained on the surface of the titanium alloy ball head, a main channel connected to the main hole and a branch network channel connected to the main channel are obtained, and the top position of the branch network channel is pre-positioned; S2, using a laser post-processing process to obtain a first pit texture: mechanically polishing the surface of the titanium alloy ball head obtained in the previous step, combining the top position of the branch network channel obtained in the previous step, using a laser process to prepare a first pit on the surface of the titanium alloy ball head, and connecting the bottom of the first pit with the top of the branch network channel; using a laser process, preparing an annular groove surrounding part of the first pit and the second pit on the surface of the titanium alloy ball head; S3, high-pressure gas cleaning: Use high-pressure gas to flush the main hole and the first pit on the surface of the titanium alloy ball head, and clean the adhered powder inside the main channel and the branch network channel; Furthermore, in step S3, the high-pressure gas first enters the main channel from the main hole, and then is discharged through the branch network channel and the first pit; then the high-pressure gas reverses the operation, enters the branch network channel from the first pit, and then is discharged through the main channel and the main hole.
[0016] S4, pre-filling of nano solid particles: filling the main channel and the branch network channel with nano hydroxyapatite and / or nano MoS2 particles mechanically through the main hole in the middle of the surface of the titanium alloy ball head; using pressurization to achieve the filling of the first pit of the titanium alloy ball head with nano hydroxyapatite and / or nano MoS2 particles from the bottom of the first pit.
[0017] Furthermore, in step S4, the nano-hydroxyapatite and / or nano-MoS2 particles are uniformly mixed with medical alcohol into a viscous state before filling, and the main channel and the branch network channel are first filled by gravity and centrifugal force; then dry high-pressure gas is input to achieve rapid volatilization and discharge of the medical alcohol; for the case where the main channel and the first pit are pre-filled with simulated body fluids, gravity and centrifugal force are used to achieve the filling of the simulated body fluids.
[0018] Compared with the prior art, the technical solution of a titanium alloy artificial joint and a processing method thereof of the present invention has the following advantages: First, in the technical solution of the present invention, the titanium alloy ball head surface can obtain better tribological properties through a specific structural design, and achieve a longer service life of the artificial joint. The combined design of the first pit and the second pit, the main channel and the branch network channel realize the effective transportation and supply of solid particles and body fluids, and the filling component of MoS2, so that during the friction and wear process, MoS2 particles can be dispersed and transferred on the friction surface of the ball head through the first pit, and effective antibacterial is achieved while reducing friction and lubrication. The first pit texture itself can use different texture processing methods and texture structure arrangements, as well as MoS2 to pre-fill the structure to reduce wear, reduce wear debris, and prevent joint inflammation. The first pit texture serves as a source of lubricating medium, while the second pit texture has a wear debris storage function, avoiding the influence of wear debris on the movement of human joints and causing inflammation problems. MoS2 itself is a very good solid lubricant, and its easy-to-slide microstructure is used to achieve friction reduction and lubrication. Cu ions can also combine with proteins in the human body to form a thin layer of lubricating layer, forming effective fluid lubrication on the surface of the ball head. The present invention simultaneously fills Cu and MoS2, which can realize the superposition of multiple lubrication forms and the consideration of bactericidal effect.
[0019] Second, in the technical solution of the present invention, the titanium alloy head handle only plays a fixing role, and there is no need to consider the wear problem. Therefore, a certain proportion of the texture is filled with hydroxyapatite and / or MoS2 particles, and the osteogenic properties of the large-pore texture and the osteogenic properties and antibacterial effects of the hydroxyapatite and / or MoS2 particles in the filled texture are comprehensively utilized. Hydroxyapatite has good osteogenic properties, and large-pore textures exceeding 300 microns can also promote osteogenic properties. At the same time, the space of the large-pore texture makes the combination between the ball handle and the human skeleton more firm, so hydroxyapatite and unfilled large-pore texture can achieve synergistic effects in osteogenic properties; MoS2 has a good antibacterial effect and can also play a synergistic role with hydroxyapatite.
[0020] Third, in the technical solution of the present invention, the texture structure is processed on demand by combining 3D printing integrated molding and laser post-processing, which realizes effective filling and long-term lubrication of filling particles at different positions. The second pit texture of the ball head and the large-aperture texture of the ball handle can be prepared by 3D printing integrated molding, which reduces the later laser texturing processing steps. At the same time, the inside and edge of the pit texture are relatively rough, which is more conducive to the adhesion of filling particles. In the present invention, a small amount of wear debris may be generated by the long-term movement and friction of the artificial joint, and the second pit texture can well meet the collection and storage of wear debris. The ball head needs to frequently make relative movements during the movement of the artificial joint, and the rotation amplitude of the ball head is large. The filled hydroxyapatite, MoS2 and Cu particles may fall out of the second pit texture after a certain period of time. The existence of the annular groove can hinder and inhibit the large-scale transfer of such particles as filling particles and wear debris, limit them to a smaller range, and realize the reciprocating adhesion and transfer of the MoS2 and / or Cu particles filled in the pit texture in a certain area of the grinding pair surface during the repeated contact with the grinding pair surface during the friction process, thereby realizing effective lubrication and antibacterial of the friction surface, and finally achieving long-term effective lubrication and antibacterial.
[0021] Fourth, in the technical solution of the present invention, the overall covering hydroxyapatite coating and MoS2 coating prepared on the surface of the artificial joint in the prior art are replaced with nano-scale particles, which have better adaptability. On the one hand, the nano-scale granular hydroxyapatite, MoS2 and Cu nanoparticles filled in the first pit texture can make full use of the adhesion and diffusivity of the nanoparticles to achieve the effective existence of these particles on the surface of the artificial joint, and under the force and heat action during the friction process, they are continuously squeezed out from the first pit to achieve better and longer-term effects; on the other hand, for the ball head part, compared with the large-area coating coverage, the granular filling will not cause the coating to fall off locally in large pieces due to the bonding strength, and the resulting joint activity abnormalities and inflammation. The particle filling process can more effectively exert the biocompatibility of the titanium alloy matrix, and further can also be combined with the surface hardening modification, and the texture to collect the wear debris, significantly improving the comprehensive performance of the artificial joint.
[0022] Fifth, in the technical solution of the present invention, a combination of metal 3D printing and laser post-processing technology is used to realize the preparation and connection of the main channel and the pit texture, which can realize the effective and continuous supply of filling particles and body fluids. The preparation method of the present invention, by cleverly combining processing techniques, can simultaneously obtain the main channel and branch network channel for storing body fluids or nanoparticles. The gravity and centrifugal force after mixing with medical alcohol are used to efficiently realize the filling of hydroxyapatite, MoS2 and Cu nanoparticles, obtain the first pit for long-term delivery of body fluids or nanoparticles to the friction surface of the artificial joint, and obtain the large-diameter second pit for promoting osteogenesis and collecting wear debris. The present invention is more suitable for the long-term service of artificial joints in the human body, and can be combined with the need to introduce and continuously release the drugs required for implantation in the human body in the main channel, inhibit rejection and inflammation, and improve the compatibility of human joints with the human body more conveniently and efficiently. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the overall structure of the titanium alloy artificial joint of the present invention; Figure 2 It is a structural schematic diagram of the main channel and the first pit of the titanium alloy artificial joint of the present invention; Figure 3 A schematic diagram of the surface structure of a titanium alloy ball head according to the present invention; Figure 4 This is a schematic diagram of the 3D printed structure of the main channel and branch network channel of the titanium alloy artificial joint of the present invention; Figure 5 It is a cross-sectional schematic diagram of the annular groove structure of the titanium alloy ball head of the present invention. DETAILED DESCRIPTION
[0024] See also Figure 1-Figure 5A titanium alloy artificial joint of the present invention comprises a titanium alloy head handle 2 and a titanium alloy ball head 1, which are integrally fixedly connected with each other and are integrally formed by titanium alloy 3D printing; at least one main hole 10 is provided in the middle of the surface of the titanium alloy ball head 1, and a plurality of branch network channels 31 are also provided inside the titanium alloy ball head 1, and a main channel 3 with a closed bottom is provided inside the titanium alloy head handle 2; the main hole 10 passes through the titanium alloy ball head 1 and is connected to the main channel 3 inside the titanium alloy head handle 2; the outer surface of the titanium alloy ball head 1 is also provided with a first pit 11 and a second pit 12; the first pit 11 The diameter of the second pit 12 is 10-100 microns, and the diameter of the second pit 12 is 300-1000 microns; the two ends of the branch network channel 31 are respectively connected to the bottom of the first pit 11 and the main channel 3; the bottom of the second pit 12 is closed; the outer surface of the titanium alloy ball head 1 is also provided with at least one annular groove 13 with a width not exceeding 100 microns; the main hole 10, the main channel 3 and the branch network channel 31 are all prepared by a one-step metal 3D printing method; the main channel 3, the branch network channel 31 and the first pit 11 are pre-filled with nano-hydroxyapatite and / or nano-MoS2 particles; the second pit 12 is not filled.
[0025] It should be noted that the sizes of the circles representing the pits and micropores in the accompanying drawings are only schematic diagrams and do not represent the actual sizes.
[0026] Preferably, the diameter of the first pit 11 is 10 microns, 30 microns, 50 microns, 70 microns or 100 microns, the diameter of the second pit 12 is 300 microns, 500 microns, 700 microns or 1000 microns; the width of the annular groove 13 is 10 microns, 30 microns, 50 microns, 70 microns or 100 microns.
[0027] Furthermore, nano Cu particles are pre-filled in the main channel 3, the branch network channel 31 and the first pit 11. On the one hand, the Cu nanoparticles themselves are also very good solid lubricants. On the other hand, Cu ions can also react with human proteins to form a thin layer of lubricating film, further improving the lubrication effect. In practical applications, based on the actual conditions such as the patient's physical condition and exercise habits, you can choose to fill MoS2 nanoparticles and Cu nanoparticles in any texture at the same time, or only fill one of them separately. The presence of the annular groove effectively avoids the large-scale spillage and consumption of the filled MoS2 and / or Cu particles in a short period of time due to large-scale rotation and friction during the friction and wear of the ball head; and under the action of reciprocating friction, the MoS2 and / or Cu particles filled in the first pit texture gradually adhere to and transfer to the surface of the grinding pair, and are brought to the friction surface of the texture-free area of the ball head during the friction process, thereby achieving comprehensive and effective lubrication and antibacterial of the friction surface.
[0028] Preferably, the particle size of the hydroxyapatite, MoS2 and Cu nanoparticles is 50 nanometers, 100 nanometers, 300 nanometers or 500 nanometers.
[0029] Furthermore, the main channel 3 and the first recess 11 are pre-filled with simulated body fluids; as a preferred embodiment, anti-inflammatory drugs may be added to the simulated body fluids to slowly release the drug effects after implantation into the human body.
[0030] Furthermore, the first pit 11 is prepared by laser post-processing; preferably, a laser marking machine is used to perform laser processing on the surface of the titanium alloy ball head prepared by 3D printing, and multiple laser post-processing is required according to the depth of the first pit until the bottom of the first pit is connected to the branch network channel at the corresponding position; during the laser post-processing process, the laser position is fixed, and the titanium alloy ball head moves and rotates along the set trajectory with the workpiece base to achieve the preparation of the first pit.
[0031] The first pits 11 and the second pits 12 are arranged regularly to form a texture on the surface of the titanium alloy ball head 1; as needed, the diameters of the first pits 11 in different areas are the same or different, and the diameters of the second pits 12 in different areas are the same or different; the second pits 12 are prepared by laser post-processing or by a one-step 3D metal printing method, and the depth of the second pits 12 is determined according to actual conditions, preferably, the depth ranges from 100 to 300 microns.
[0032] Preferably, the first pits 11 and the second pits 12 are alternately and evenly distributed with the main hole 10 as the center.
[0033] Furthermore, the surface of the titanium alloy head handle 2 is provided with micropores 21 with a diameter of 300-600 microns, a depth of 100-300 microns, a micropore surface density of 10%-50%, and the micropores are regularly arranged to form a texture, and some of the micropores 21 are filled with nano-hydroxyapatite and / or nano-MoS2 particles. Preferably, the proportion of micropores 21 filled with nano-hydroxyapatite and / or nano-MoS2 is 5%-30%; further preferably, the proportion of micropores 21 filled with nano-hydroxyapatite and / or nano-MoS2 is 5% or 10% or 15% or 20% or 25% or 30%. Only a part of the micropores 21 is filled, but not all of them. The purpose is to make full use of the osteogenic effect of the large-diameter micropores themselves and the osteogenic and anti-inflammatory effects of the filling particles, so as to achieve a rapid and good combination of the titanium alloy head handle and the human body to a greater extent.
[0034] Both the large pore texture and hydroxyapatite contribute to the improvement of osteogenic performance, and the second pit on the surface of the ball head and the microporous structure on the surface of the ball handle both adopt large pore texture, so that the combination between the ball head, the ball handle and the human skeleton is more solid, and the hydroxyapatite and the unfilled large pore texture can achieve synergistic effect on osteogenic performance, and the presence of MoS2 can further improve the antibacterial performance. MoS2 and Cu have excellent bactericidal functions and are also good solid lubricants. During the friction and wear process of the ball head, MoS2 and / or Cu particles can be dispersed and transferred on the friction surface and near the ball head to achieve effective lubrication and antibacterial. The titanium alloy artificial joint in the present invention application is mainly aimed at the artificial joint of the ball head and the head handle structure. In practical applications, the technical solution of the present invention application can be applied to other types of artificial joints after adaptive adjustment.
[0035] Further, the diameter of the main hole 10 is 1000-3000 microns, preferably, the diameter of the main hole 10 is 1000 microns or 1500 microns or 2000 microns or 2500 microns or 3000 microns; the inner diameter of the main channel 3 is 1000-3000 microns, preferably, the inner diameter of the main channel 3 is 1000 microns or 1500 microns or 2000 microns or 2500 microns or 3000 microns; the top diameter of the branch network channel 31 is 500-1000 microns, preferably, the top diameter of the branch network channel 31 is 500 microns or 700 microns or 900 microns or 1000 microns, further preferably, the inner diameter of the end of the branch network channel 31 connected to the main channel is not less than the inner diameter of the end connected to the first pit, preferably, the inner diameter of the end of the branch network channel 31 connected to the main channel is consistent with the inner diameter of the main channel, thereby achieving smooth supply of nano solid particles and body fluids filled in the main channel to the first pit.
[0036] Furthermore, the area surrounded by any annular groove 13 has a first pit 11 and a second pit 12 .
[0037] See also Figure 5 , the axis of the titanium alloy ball head itself presents a certain angle with the vertical direction, showing a forward tilted state. The depth direction of the annular groove also has a certain angle with the axis of the titanium alloy ball head itself, and the depth direction of the annular groove is roughly close to the axis of the titanium alloy head handle in the vertical direction, which enables the annular groove 13 to store MoS2 nanoparticles, Cu nanoparticles and nanohydroxyapatite in the depth direction for a longer time during the service of the artificial joint, and the collected particles will not be easily removed from the annular groove due to the inclination of the titanium alloy ball head itself and its rotation process, so that the MoS2 nanoparticles, Cu nanoparticles and nanohydroxyapatite can play a role for a longer time. Further, the annular groove 13 is vertically downward in the depth direction.
[0038] Furthermore, the depth of the first pit 11 is 100-300 microns. This depth allows the thickness between the top of the branch network channel and the surface of the titanium alloy ball head to be relatively easy to open up the bottom of the first pit during laser post-processing, while also being able to form the required first pit on the surface of the titanium alloy ball head, thereby becoming an output channel for nanoparticles and simulated body fluids.
[0039] Furthermore, in another preferred embodiment, a cover (not shown in the figure) is provided on the surface of the main hole to close the main hole; after the main channel is filled with solid nanoparticles and / or body fluids, the main hole 10 is closed with the cover, so that the solid nanoparticles and body fluids filled in the main channel will not appear in large quantities from the main hole 10 on the surface of the titanium alloy ball head, resulting in insufficient long-term action of the solid nanoparticles and body fluids; the cover is made of a material commonly used in artificial joints, preferably, the cover is made of ultra-high molecular weight polyethylene or PEEK; after the cover is installed, its upper surface is lower than the surface of the titanium alloy ball head at the adjacent position, so that the titanium alloy ball head will not contact the surface of the cover during friction, ensuring that the cover itself will not wear, thereby achieving the main hole 10 remaining closed during service.
[0040] Preferably, a method for processing a titanium alloy artificial joint of the present invention comprises the following steps: S1, 3D printing one-step molding to obtain the main body of titanium alloy artificial joint: Renishaw AM400 metal 3D printer was used to select TC4 alloy powder produced by Falcon Rapid Manufacturing Technology Co., Ltd. (measured particle size D10 = 19.46 μm, D50 = 38.95 μm, D90 = 61.52 μm, tap density 2.77 g / cm3, loose density 2.34 g / cm 3 , fluidity 39.74 s / 50g), a selective laser cladding process (SLM process preferred parameters: laser diameter 70 μm, laser power 200 W, exposure time 80 μs, point spacing 50 μm, line spacing 75 μm, layer thickness 50 μm) is used to print the titanium alloy head handle 2 and the titanium alloy ball head 1 in one step, a main hole 10 and a second pit 12 are obtained on the surface of the titanium alloy ball head 1, and micropores 21 are obtained on the surface of the titanium alloy head handle 2, connecting the main channel 3 of the main hole 10 and the branch network channel 31 connected to the main channel 3, and the top position of the branch network channel 31 is pre-positioned, so as to facilitate the determination of the position when preparing the first pit 11 in the later laser post-processing; S2, using laser post-processing technology to obtain the first pit texture: grinding and polishing the outer surfaces of the titanium alloy head handle 2 and the titanium alloy ball head 1 obtained in the previous step, so that the roughness of the texture-free area does not exceed 5 microns; combining the top position of the branch network channel 31 obtained by positioning in the previous step, using laser technology, prepare the first pit 11 on the surface of the titanium alloy ball head 1, and connect the bottom of the first pit 11 with the top of the branch network channel 31; using laser technology, prepare an annular groove 13 surrounding part of the first pit 11 and the second pit 12 on the surface of the titanium alloy ball head 1; polishing the surface of the obtained titanium alloy ball head 1, and removing the texture edge protrusions formed in the process of preparing the first pit texture by laser post-processing; experimental studies have found that the texture edge protrusions have a good effect of improving wear resistance, but in the technical solution of the present invention, considering that it will cause more scratches on the surface of the grinding pair, which is not conducive to the early running-in and adaptation experience of the artificial joint titanium alloy ball head with the human joint after implantation into the human body, the present invention applies for special grinding and removal of the texture edge protrusions in advance; S3, high-pressure gas cleaning: high-pressure gas is used to flush the main hole 10 and the first pit 11 on the surface of the titanium alloy ball head 1, respectively, to clean the adhered powder inside the main channel 3 and the branch network channel 31; Furthermore, in step S3, the high-pressure gas first enters the main channel from the main hole 10, and then is discharged through the branch network channel 31 and the first pit 11; then the high-pressure gas reverses the operation, and enters the branch network channel 31 from all the first pits 11 at the same time, and then is discharged through the main channel 3 and the main hole 10, so that the first pits, the branch network channels and the main channel are interconnected, so that during the service of the artificial joint, the solid nanoparticles and body fluids filled in the main channel can enter the first pits through the branch network channels in time, and be transported and supplied from the first pits to the entire titanium alloy ball head surface; S4, pre-filling of nano solid particles: fill the main channel 3 and the branch network channel 31 with nano hydroxyapatite and / or nano MoS2 particles and / or nano Cu particles by mechanical means through the main hole 10 in the middle of the surface of the titanium alloy ball head 1; use pressurization to achieve the filling of the first pit 1 with nano hydroxyapatite and / or nano MoS2 particles and / or nano Cu particles from the bottom of the first pit 11 of the titanium alloy ball head 1; use mechanical means to fill some of the micropores 21 with nano hydroxyapatite and / or nano MoS2 particles.
[0041] Furthermore, in step S4, the nano-hydroxyapatite and / or nano-MoS2 particles and / or nano-Cu particles are uniformly mixed with medical alcohol into a viscous state before filling, and the main channel 3 and the branch network channel 31 are first filled by gravity and centrifugal force; then dry high-pressure gas is input to achieve rapid volatilization and discharge of the medical alcohol; for the case where the main channel 3 and the first pit 11 are pre-filled with simulated body fluids, gravity and centrifugal force are used to achieve the filling of the simulated body fluids.
[0042] As another preferred embodiment, the outer surface of the titanium alloy ball head 1 has a nitriding layer. In this embodiment, the main channel, the branch network channel, the first pit and the second pit are prepared first, and then ion nitriding treatment is carried out, and finally nanoparticles and body fluids are filled; since the nitriding layer is not completely covered by other coatings, the high hardness of the nitriding layer can be directly used to further improve the wear resistance of the titanium alloy ball head surface and reduce the generation of wear chips and possible inflammation; the nitriding treatment is carried out in an ion nitriding furnace, and the preferred main process parameters include 800-900 V working voltage, 10-12 A current, 500-600 Pa furnace pressure, 750-850°C, 6-8 h, NH3 nitrogen atmosphere, to obtain a nitriding layer with a thickness of not less than 0.1 mm, and a microhardness test is carried out under 200g force conditions. The hardness range of the obtained nitriding layer is 800HV-1200HV.
[0043] The main channel and the branch network channel can be used as storage space for MoS2 nanoparticles, Cu nanoparticles and nanohydroxyapatite. During the friction process of the ball head, the first pit texture 11 can be used to supply MoS2 nanoparticles, Cu nanoparticles and nanohydroxyapatite to the friction surface of the ball head for a long time to achieve lubrication, sterilization and promote osteogenesis. In terms of the combination of nanoparticles, MoS2 nanoparticles, Cu nanoparticles and nanohydroxyapatite can be combined according to the implantation conditions of different artificial joints, so as to select one, two or three of them for filling. The large diameter design of the second pit itself promotes osteogenesis, and can also be used to collect and store a small amount of wear debris generated by the friction of the ball head to avoid inflammation. The first pit texture and the second pit texture cooperate with each other to achieve effective lubrication, reduce wear debris and control inflammation.
[0044] A titanium alloy artificial joint and a processing method thereof of the present invention, combined with different texture combinations, ion nitriding hardening, and nanoparticle filling, effectively improves its wear resistance, osteogenic performance and antibacterial performance, especially simultaneously utilizes the friction reduction, lubrication and antibacterial effects of MoS2 and Cu nanoparticles, and the osteogenic promotion effect of hydroxyapatite and large-size textures, so that during the friction and wear process, the nanoparticles can be dispersed and transferred on the friction surface and near the ball head to achieve effective lubrication and antibacterial; compared with the overall covering hydroxyapatite coating and MoS2 coating prepared on the surface of the artificial joint in the prior art, the present invention replaces the coating coverage with particle filling, has better adaptability, and the granular filling texture will not cause the coating to fall off locally in large pieces due to the bonding strength, and the abnormal joint movement and inflammation caused by it; the particle filling treatment can more effectively exert the biocompatibility of the titanium alloy matrix; the tribological modification after the surface hardening modification, and the collection effect of the texture on wear debris, both significantly reduce the intensity of its friction. By cleverly combining different processing techniques, the main channel, branch network channel and the first pit are interconnected, so that the surface of the titanium alloy ball head can achieve timely and long-term supply of nanoparticles such as MoS2, Cu, hydroxyapatite, etc., thereby obtaining a titanium alloy artificial joint with a longer life.
Claims
1. A titanium alloy artificial joint, comprising a titanium alloy head handle and a titanium alloy ball head, characterized in that: The titanium alloy head handle and the titanium alloy ball head are integrally fixedly connected; at least one main hole is provided in the middle of the surface of the titanium alloy ball head, and a plurality of branch net channels are provided inside the titanium alloy ball head, and a main channel with a closed bottom is provided inside the titanium alloy head handle; the main hole is connected to the main channel inside the titanium alloy head handle; a first pit and a second pit are provided on the outer surface of the titanium alloy ball head; the two ends of the branch net channel are respectively connected to the bottom of the first pit and the main channel; the bottom of the second pit is closed; at least one annular groove is provided on the outer surface of the titanium alloy ball head; the main channel and the first pit are pre-filled with nano-hydroxyapatite and / or nano-MoS2 particles; the second pit is not filled.
2. A titanium alloy artificial joint according to claim 1, characterized in that: The main channel, the branch network channel and the first recess are also pre-filled with simulated body fluid.
3. The titanium alloy artificial joint according to claim 1, characterized in that: The first dimple is prepared by laser post-processing; the first dimple and the second dimple both form textures on the surface of the titanium alloy ball head.
4. The titanium alloy artificial joint according to claim 1, characterized in that: The surface of the titanium alloy head handle is provided with micropores with a diameter of 300-600 microns, and some of the micropores are filled with nano-hydroxyapatite and / or nano-MoS2 particles.
5. The titanium alloy artificial joint according to claim 1, characterized in that: The diameter of the main hole is 1000-3000 microns; the inner diameter of the main channel is 1000-3000 microns, and the top diameter of the branch network channel is 500-1000 microns.
6. The titanium alloy artificial joint according to claim 1, characterized in that: The area surrounded by any annular groove has a first pit and a second pit.
7. The titanium alloy artificial joint according to claim 1, characterized in that: The depth of the first pit is 100-300 microns.
8. The method for processing a titanium alloy artificial joint according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1, 3D printing one-step molding to obtain the titanium alloy artificial joint body: a metal 3D printer is used to print the titanium alloy head handle and the titanium alloy ball head in one step, a main hole and a second pit are obtained on the surface of the titanium alloy ball head, a main channel connected to the main hole and a branch network channel connected to the main channel are obtained, and the top position of the branch network channel is pre-positioned; S2, using a laser post-processing process to obtain a first pit texture: mechanically polishing the surface of the titanium alloy ball head obtained in the previous step, combining the top position of the branch network channel obtained by positioning in the previous step, using a laser process to prepare a first pit on the surface of the titanium alloy ball head, and connecting the bottom of the first pit with the top of the branch network channel; S3, high-pressure gas cleaning: Use high-pressure gas to flush the main hole and the first pit on the surface of the titanium alloy ball head, and clean the adhered powder inside the main channel and the branch network channel; S4, pre-filling of nano solid particles: filling the main channel and the branch network channel with nano hydroxyapatite and / or nano MoS2 particles mechanically through the main hole in the middle of the surface of the titanium alloy ball head; using pressurization to achieve the filling of nano hydroxyapatite and / or nano MoS2 particles from the bottom of the first pit of the titanium alloy ball head to the first pit.
9. The method for processing titanium alloy artificial joints according to claim 8, characterized in that: In step S3, the high-pressure gas first enters the main channel from the main hole, and then is discharged through the branch network channel and the first pit; then the high-pressure gas reverses the operation, enters the branch network channel from the first pit, and then is discharged through the main channel and the main hole.
10. The method for processing titanium alloy artificial joints according to claim 8, characterized in that: In step S4, nano-hydroxyapatite and / or nano-MoS2 particles are uniformly mixed with medical alcohol into a viscous state before filling, and the main channel and the branch network channel are first filled by gravity and centrifugal force; then dry high-pressure gas is input to achieve rapid volatilization and discharge of medical alcohol; for the case where the main channel and the first pit are pre-filled with simulated body fluid, gravity and centrifugal force are used to achieve filling of the simulated body fluid.